شاہ ولی اللہ دہلویؒ کے منہجِ مقاصدی اور اسرار شریعت کا تجزیاتی مطالعہ : Shāh Walī Allāh al-Dehlawī’s Maqāṣid-Based Methodology and the Secrets of Sharīʿah: An Analytical Study - Muhammad Kausar; Rubina Kausar; Muhammad Idrees (International Research Journal of Arabic and Islamic Studies, 2024)
This article explores the concept of "Tafsir bil-Ma'thoor," a method of Quranic exegesis that relies on traditional narratives and established interpretations derived from the Prophet Muhammad (PBUH) and his companions. It highlights the significance of authentic Hadith and historical context in understanding the Quranic text. The article examines Mufti Saeed Ahmed Palanpuri's perspective on Tafsir bil-Ma'thoor, emphasizing its role in preserving the integrity of Quranic interpretation. By analyzing key verses and their interpretations, the study underscores the importance of this method in providing a comprehensive understanding of the Quran, ensuring that interpretations remain aligned with the original teachings of Islam. The article concludes by affirming the continued relevance of Tafsir bil-Ma'thoor in contemporary Quranic studies and its contribution to the broader field of Islamic answers and commands.